Advanced interatrial block predicts recurrence of embolic stroke of undetermined source - K. Carrillo-Loza; A. Baranchuk; F. Serrano; S. Hasseb; F. Espinosa Lira; E. Soriano; A. Arauz (Neurología (English Edition), 2022)
Background: Advanced interatrial block (IAB) is an independent risk factor for ischaemic stroke. This study aimed to analyse whether advanced IAB predicts recurrence of embolic stroke of undetermined source (ESUS). Methods: 104 patients with a confirmed diagnosis of ESUS were followed up for a median period of 15 months (interquartile range, 10-48). We recorded data on clinical variables, P-wave characteristics, and presence of IAB on the electrocardiogram (ECG). ECG findings were interpreted by a blinded, centralised rater at (XXXX2). ESUS recurrence was the primary outcome variable. Results: Median age was 47 years (range, 19-85); 50% of patients were women. IAB was detected in 36 patients (34.6%); IAB was partial in 29 cases (27.9%) and advanced in 7 (6.7%). Sixteen patients (15.4%) presented stroke recurrence; of these, 5 had partial and 4 had advanced IAB (P = .01; odds ratio [OR] = 9.44; 95% confidence interval [CI], 1.88-47.46; relative risk [RR] = 4.62; 95% CI, 2.01-10.61). Median P-wave duration was longer in patients with stroke recurrence (P = .009). The multivariate logistic regression analysis identified the following independent risk factors for stroke recurrence: advanced IAB (P < .001; OR = 10.86; 95% CI, 3.07-38.46), male sex (P = .028; OR = 4.6; 95% CI, 1.18-17.96), and age older than 50 years (P = .039; OR = 3.84; 95% CI, 1.06-13.88). In the Cox proportional hazards model, the risk variables identified were age older than 50 years (P = .002; hazard ratio, 7.04; 95% CI, 2.06-23.8) and P-wave duration (per ms) (P = .007; hazard ratio, 1.02; 95% CI, 1.01-1.04). Conclusions: Advanced IAB and age older than 50 years predict ESUS recurrence. Resumen: Antecedentes: El bloqueo interatrial avanzado (BIA-a) es considerado un factor de riesgo independiente para infarto cerebral (IC). Nuestro objetivo fue analizar si el BIA-a predice recurrencia de IC en pacientes con infarto cerebral embólico de origen no determinado (ESUS). Métodos: Ciento cuatro pacientes con diagnóstico confirmado de ESUS fueron seguidos durante una mediana de 15 meses (RIQ 10-48). Los datos clínicos, las características de la onda P y presencia de BIA en electrocardiograma realizado durante el evento índice, fueron registrados. La interpretación de los electrocardiogramas se realizó de forma centralizada y ciega en (XXXX2). La recurrencia de ESUS fue el desenlace primario. Resultados: La mediana de edad de los casos fue de 47 años (rango 19-85); 50% fueron mujeres. Se encontró BIA en 36 casos (34,6%); parcial (BIA-p) en 29 (27,9%) y BIA-a en 7 (6,7%). Dieciséis pacientes (15,4%) presentaron IC recurrente; de los cuales 5 tenían BIA-p y 4 BIA-a (p = 0,01;OR 9,44: IC 95% 1,88-47,46). La mediana de duración de la onda P fue mayor en pacientes con recurrencia (p = 0,009). En el análisis multivariado de regresión logística, los factores de riesgo independientes para recurrencia de IC fueron: el BIA-a (p < 0,001; OR 10,86: IC 95% 3,07-38,46), género masculino (p = 0,028; OR 4,6: IC 95% 1,18-17,96) y la edad mayor a 50 años (p = 0,039; OR 3,84: IC 95% 1,06-13,88); en riesgos proporcionales de Cox fueron: edad mayor a 50 años (p = 0,002; HR 7,04: IC 95% 2,06-23,8) y duración de la onda P (por ms) p = 0,007 (HR 1,02: IC 95% 1,01-1,04). Conclusiones: El BIA-a y edad mayor a 50 años predicen recurrencia de ESUS.